Familal Ties and Women Electability in the Legislative Election in 2019: Insight from South Sumatera - Alva Beriansyah; Mariatul Qibtiyah (Jurnal Studi Sosial dan Politik, 2023)
The involvement of women in the political sphere will improve the quality of democracy in Indonesia. Women have the same political rights as men to actively participate in democracy by becoming political contestants, especially in the 2019 elections. The advancement of women legislative candidates to become state officials is something that needs to be appreciated amidst the patriarchal culture that is still inherent in Indonesia. The presence of women in politics cannot be separated from the role of men. This then becomes the focus and purpose of this article, which is to describe the familial ties that are attached to the electability of women in politics. The research method used in this article is a qualitative research method that is descriptive to explain the familial ties factor for women in political power, both as members of the DPR RI and DPD RI from South Sumatra in the 2019 elections. According to Richter, familial ties are the influence of male relatives (whether fathers, fathers-in-law, brothers, uncles, or husbands) who are influential and powerful politicians, who facilitate a woman politician to build and achieve certain political leadership roles and this can be seen in the campaign periods for legislative candidates, starting from placing billboards or posters for legislative candidates that include family names behind their real names, then using political party attributes such as political party colors for women whose relatives hold positions in political parties, up to involving relatives of political officials in campaigns carried out to the public. The existence of these familial ties is inseparable from the political capital owned by the elected candidates which should also be followed by their quality and capability in the political field so that it will avoid the impression of KKN (corruption, collusion, nepotism) where the families of officials who are considered to perpetuate their hegemony in the local political sphere.